Navigating and adapting the History curriculum as an official policy to realities on the ground in Eswatini, Waterford Kamhlaba United World College (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
History is one of the most valuable subjects in the school curriculum. History plays a vital role in facilitating the political, social and economic development of Eswatini through the improvement of life skills such as empathy, tolerance, critical thinking, communication and proper decision-making. It is the responsibility of teachers to navigate the History curriculum and adapt it as an official policy to realities on the ground, thus yielding responsible citizens. This article outlines various strategies that teachers can implement to fulfil this responsibility.
Keywords: History; school curriculum; Eswatini; teachers; official policy